(untitled) (Revista da Faculdade de Odontologia - UPF, 2020)
Sialolithiasis is the most common form of obstructive sialadenitis caused by a mixture of different calcium phosphates and an organic matrix. It is one of the most common salivary gland diseases, often attributed to the submandibular gland, with no relation to age or gender. However, it is rarely reported in the minor salivary glands. A 43-year-old female patient presented with a single, yellow and asymptomatic nodule in the labial mucosa at clinical examination. The clinical hypotheses were lipoma and fibrous hyperplasia. The lesion was biopsied, and the histopathological analysis showed a mineralized tissue. The final diagnosis was sialolithiasis and the patient remained under follow-up (8 months) without relapse. This case shows that sialolithiasis should be included in the diagnostic hypotheses when occur in a minor salivary glands area and emphasizes the importance of a complete clinical examination since it was not complaint of the patient.